Case Report: Pulmonary arterial hypertension in children caused by a new mutation in the BMPR2 gene - Tang, Ting; Wu, Shuqi; Peng, Chang; Wang, Li (Frontiers in Pediatrics, 2025)
Pulmonary arterial hypertension (PAH) is a rare and severe condition that has been linked to hereditary factors. Mutations in the gene encoding bone morphogenetic protein receptor 2 (BMPR2) have been identified as a cause of heritable PAH. We report the discovery of a novel point mutation combined with a deletion insertion mutation (c.621+2T>C/c.621+5_621+11delinsA) in the BMPR2 gene of an 11-year-old PAH patient lacking a family history of genetic disease (Clinical trial number: not applicable). This report expands the genetic landscape and offers a scientific foundation for early disease detection, personalized treatment strategies, and genetic counseling.